AI-Driven Predictive Analytics for Workforce Planning and Optimization - Nishitha Reddy Nalla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Predictive analytics powered by AI is revolutionizing the way organizations plan and optimize their workforce. Through the use of big data, machine learning and AI technologies, organizations can forecast workforce requirements, improve talent management techniques, and drive operational effectiveness. In recent years, the integration of AI-driven predictive analytics in workforce planning and optimization has transformed the way organizations manage talent, enabling them to adapt quickly to changing demands. It also explores the future of AI in human resource management, offering guidance on the ’Innovation Roadmap’ to help organizations as they evolve.